Reconceiving the Intellectual’s Role: A Critical Analysis of Beginnings by Edward Said - BEN KHALIFA Hamza; BEN KHALIFA Hamza (University of Eloued جامعة الوادي, 2025)
This study investigates Edward Said’s redefinition of the intellectual’s role through his theory of beginnings in Beginnings: Intention and Method (1975), analyzing how his critique of static origins in favor of contingent, dynamic beginnings reshapes intellectual agency. Employing textual hermeneutics and conceptual analysis, the research examines Said’s dialogues with Foucault, Derrida, and Vico, situating his work within poststructuralist and postcolonial debates to assess whether his secular critique reconciles structuralist thought with the ethical demands of cultural criticism. The findings reveal that Said’s framework reconfigures the intellectual as both critical outsider and politically engaged scholar, using contingency and secular critique to dismantle hegemony while centering marginalized voices. The study concludes that Beginnings remains vital to contemporary cultural criticism, offering a model for intellectuals to navigate power and representation crises by bridging theory and praxis ultimately reframing intellectual responsibility as a self-reflexive, ethical struggle against systemic oppression.
Master's Degree In Literature and Civilization. 2025
Keywords: Beginnings; Contingency Origin; Human agency; Secular criticism; Intellectual’s role.